Growth of an 8-hydroxyquinoline single crystal by a modified Czochralski growth technique, and crystal characterization. Issue 5 (11th January 2018) - Kumar, Sonu; Kumar, Binay
Abstract : Piezoelectric 8-hydroxyqunoline crystal was grown by modified Czochralski set-up, designed for low melting point organic compounds. Hirshfeld surface and fingerprint plots were generated. Abstract : A novel modified Czochralski crystal growth technique for low temperature was designed with a closed chamber which allowed for variations in the environment. A large sized single crystal of 8-hydroxyquinoline with diameter 1.2 cm and length 7.4 cm was successfully grown in an argon atmosphere. Structural parameters were determined by the powder X-ray diffraction method. The functional groups were confirmed by Fourier transform infrared spectroscopy. Thermal transitions at various temperatures were measured by thermogravimetric/differential thermal analyses. The dielectric properties of the grown crystal were studied with variations of temperature and frequency. The grown crystals were found to be piezoelectric as confirmed by the d 33 coefficient of 5 pC N −1 . A Vickers microhardness study revealed that the grown crystal belongs to the soft type single crystals with a Meyer's index ( n ) of 1.98.